At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
x= 23/9
Step-by-step explanation:
(12 + 36x) - (12x + 18) = 36 + (6x + 4)
(12 - 18) + (36x - 12x) = 36 + 4 + 6x
-6 + 24x = 40 + 6x
-6 + 18x = 40
18x = 46
x = 46/18
x = 23/9
Answer:
23/9
Step-by-step explanation:
3(4 + 12x) - 6(2x + 3) = 36 + 2(3x + 2)
12 + 36x - 12x - 18 = 36 + 6x + 4
12 - 18 - 36 - 4 = -36x + 12x + 6x
-46 = -18x
x=46/18
x=23/9
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.